3MT Competition attracts PhD students to showcase their research - UMP, PNC (2019)
The Institute of Postgraduate Studies (IPS) at Universiti Malaysia Pahang (UMP) recently conducted its annual Three-Minute Thesis (3MT) Competition at the Tun Fatimah Hall of the university’s Gambang Campus on April 30, 2019.